KONTEKSTUALISASI NILAI-NILAI LUHUR WARISAN LELUHUR DI ERA GLOBAL: BELAJAR DARI SERAT TRIPAMA DAN WAHYU MAKHUTA RAMA - Ahmad Salehudin (UIN Sunan Kalijaga Yogyakarta, 2017)
Heritage is a “blue print” that not only serves as guidance, but also a parameter for its heirs to live their lives. We must behave as we have